Performance of copper oxide/distilled water nanofluid in evacuated tube solar collector (ETSC) water heater with internal coil under thermosyphon system circulations - Ghaderian, J. (Elsevier Ltd, 2017)
In this study, the effect of CuO/distilled water nanofluid on the performance of evacuated tube solar collector (ETSC) water heater with internal coil under thermosyphon system circulations was experimentally investigated. The volume fraction of nanoparticles was considered at 0.03–0.06%. The mass flow rate of water passing through the coil was varied from 20 to 60 L/h. ASHRAE standard 86–93 was considered to calculate the efficiency of the collector. From the study, we found that the efficiency of ETSC increase when the nanofluid was used as an absorption medium. CuO nanofluids at 0.03% volume fraction in ETSC gave enhancement up to 14%, when compared to water.